2003
DOI: 10.1002/hlca.200390002
|View full text |Cite
|
Sign up to set email alerts
|

14‐Membered Cyclopeptides from Paliurus ramosissimus and P. hemsleyanus

Abstract: Six 14-membered cyclopeptide alkaloids, i.e., ramosines A ± C, mucronine J, and lotusines A and D, were isolated from the roots of Paliurus ramosissimus, and an additional four, hemsines A ± D, from the roots of P. hemsleyanus. Among these, ramosines A ± C (1, 5, and 6, resp.) and hemsines A and B (7 and 8, resp.) are new bases of the amphibine-B type, and hemsines C and D (9 and 10, resp.) are new integerrine-type alkaloids. Additionally, ramosine C (6) represents the first 14-membered cyclopeptide alkaloid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…The NMR data of compound 1 (Table 1 and 2) showed great similarity with the NMR data previously reported for ramosine-A (Lin et al, 2003). Ramosine-A contains a paracyclophane.…”
Section: Resultssupporting
confidence: 82%
“…The NMR data of compound 1 (Table 1 and 2) showed great similarity with the NMR data previously reported for ramosine-A (Lin et al, 2003). Ramosine-A contains a paracyclophane.…”
Section: Resultssupporting
confidence: 82%
“…The configuration of nummularine-R ( 1 ) has been described in 2010 by Nisar et al, based on NOESY interactions, and indeed the l -configuration was found for the three amino acid units present in this cyclopeptide alkaloid . The l -configuration was also reported for hemsine-A ( 4 ) and ramosine-A ( 6 ) . In oxyphylline-C ( 8 ) the two ring-bound amino acid units were found to be present in the l -configuration as well .…”
Section: Resultssupporting
confidence: 54%
“…Compound 6 was identified as ramosine-A, mainly based on the NMR data obtained. This cyclopeptide alkaloid was previously reported from Paliurus ramosissimus , but this is the first time it has been isolated from Z. oxyphylla (batch 2). Compound 7 was reported in Z. oxyphylla by Kaleem et al and was isolated from the first batch of plant material.…”
Section: Resultsmentioning
confidence: 75%
“…[8] The use of this reaction was demonstrated by the synthesis of ap yrrolidine-derived bioactive compound via the construction of 3-hydroxy-2-alkyl-pyrrolidine, which is ap ivotal scaffold contained in various alkaloids and bioactive agents. [9][10][11] Unfortunately,t he net yield of the 3-hydroxy-2-alkylpyrrolidine wasm oderate owingt ot he modestr egioselectivity of the Eu(OTf) 3 -catalyzed aminolysis of the 3,4-epoxy alcohol, indicatingt here is room for further improvement.…”
mentioning
confidence: 99%
“…1 [b] Eu(OTf) 3 (1) PhMe (0.05) 88 %( 1h)12:1 2 [b] La(OTf) 3 (1) PhMe (0.05) 87 %( 2h)13:1 3 [b] TfOH 10PhMe (0.05) 75 %( 24 h) 11:1 4 [b] none PhMe (0.05) NR (24 h) -5La(OTf) 3 (10) MeCN (0.05) 88 %( 6h)10:1 6La(OTf) 3 (10) THF (0.05) 90 %( 18 h) 12:1 7La(OTf) 3 (10) ( endo-tet cyclization smoothly proceededi nt he presence of electron-rich and electron-deficient benzyl groups( 2ba, 2ca).…”
mentioning
confidence: 99%